Kedudukan dan Hak-Hak Anak Perempuan Dalam Hukum Kewarisan Islam - Iman Jauhari (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2016)
The woman status and rights in the inheritance law have a dissenting of opinion among scholars. Therefore, the position and rights of woman in Islamic inheritance law re-assessed. The method used is content analysis of references that is relevant to the issues discussed. Differences of opinion among scholars attributed to differences in understanding the meaning lafadh and expansion of the scope walad words contained in the verses of inheritance and influenced by pre-Islamic Arab culture (Oahiliyah). According to the Sunni scholars, women are not menghijab brother (both male and female), while according to scholars of the Shia , the word of walad include boys and girls, so the girls can also attract (menghijab) brother (both male and female). The presence of KHI has shifted the system of Islamic inheritance developed by scholars earlier patterned by the patrilineal to the bilateral inheritance system that attract the lineage from both directions from relatives of men and women .The bilateral patterned inheritance system is more in line with the kinship system in Indonesia and developments today's society.